Respons Fisiologis dan Produktivitas Tanaman Kedelai Edamame (Glycine max L. Merr.) terhadap Tingkat Cekaman Kekeringan pada Berbagai Fase Pertumbuhan - Muhamad Noor Azizu; Wahyu Setiyadi; Dendy Detafiano Prakasa Afner (Jurnal Agrosains dan Teknologi, 2026)
Soybean is one of the economically important crops with continuously increasing demand. However, under Indonesian agroclimatic conditions, drought stress remains a major limiting factor in soybean cultivation systems. This study aimed to evaluate the physiological responses and growth dynamics of edamame soybean under different levels and timing of drought stress in order to identify the most sensitive growth stage and determine the level of drought stress that can still be tolerated without causing significant yield reduction under tropical environmental conditions. The experiment was arranged in a factorial randomized complete block design (RCBD) with two factors. The first factor was drought stress level, consisting of four levels: 100%, 75%, 50%, and 25% of field capacity. The second factor was the timing of drought stress application, consisting of four stages: no stress, active vegetative stage, early flowering stage, and pod filling stage. Each treatment combination was replicated three times, resulting in 48 experimental units. The observed parameters included relative water content (RWC), leaf chlorophyll content, plant height, leaf area, total dry weight, relative growth rate (RGR), net assimilation rate (NAR), number of flowers per plant, number of pods per plant, and pod weight per plant. The results showed that drought stress level and timing significantly affected physiological responses (RWC and chlorophyll content), plant morphology (plant height), and showed significant interactions on generative parameters (yield components) of edamame soybean. Mild drought stress (75% field capacity) applied during the vegetative stage still maintained relatively high RWC, number of flowers, number of pods, and pod weight per plant, indicating a greater tolerance to drought stress compared with other treatment combinations. Total dry weight, relative growth rate, and net assimilation rate began to decline from the rapid vegetative growth phase toward the early reproductive stage.